(untitled) (Indo-MathEdu Intellectuals Journal, 2023)
The implementation of Tatanen-based character development at Bale Atikan is expected to be able to produce graduates with noble character. The purpose of this research is to analyze TDBA-based character education management in improving the quality of creative and innovative junior high school graduates using qualitative methods. In this case, the population in this study are school principals, school committees, teachers, education personnel, student representatives and parent/guardian representatives. Data analysis was carried out through data reduction, data presentation and drawing conclusions. The research subjects were part of the population at SMPN 10 Purwakarta, SMPN 2 Pasawahan, and SMPN 3 Purwakarta. The results of the study revealed that (1) character program planning in these three schools focused on long and medium term development plans, with vision, mission, and clear goals; (2) the implementation of character development refers to a curriculum that supports the school’s vision and mission; (3) TDBA-based character education management evaluation is carried out effectively, involving all components in planning, implementation, and evaluation; (4) obstacles in implementing character education involve internal and external factors; (5) efforts to overcome obstacles involve the provision of facilities and infrastructure, teacher training, and improvement of character education management; (6) TDBA-based character education in the three schools produced a positive impact, including improving students’ academic results, skills, and attitudes.